Innovation in agri-food systems – A systematic mapping of the literature (1997-2017) - Innovation at system level in agri-food. Meta-table of key elements categorized in mapping study (1997-2017) - Fernqvist, Fredrik; Spendrup, Sara (Swedish University of Agricultural Sciences, 2019)
This study systematically explores, analyses, reports on and synthesises research on the topic of sectoral innovation systems related to agriculture and agri-food in OECD countries. It is based on systematic mapping of the literature (academic papers published in scientific journals) in the period 1997-2017. The aim is to show the state of current knowledge on sectoral innovation systems in agri-food, in order to identify knowledge gaps and future areas for research and provide methodological and theoretical perspectives. Abstracts for a total of 320 papers were analysed, using a qualitative approach. Key elements of agricultural innovation systems identified were organised into 8 main themes/topics: agents, basic technologies, knowledge and learning processes, mechanisms of interaction, institutions, end-users, system transition and contextual variables. Areas identified as requiring research included making the sector more consumer- and market-oriented, increasing interactions outside conventional system boundaries, including the consumer perspective and societal changes, and determining the role of gender in innovation in agri-food systems.

Key elements in the 320 items included in the mapping were recorded, based on the abstracts. The key elements, subject or main findings were then summarised in a qualitative interpretation based on the abstracts.

The key elements were thematised and categorised following the thematic analysis method. This process was performed manually, using an ordinary word processor and the recorded key elements from the Excel sheet. The elements were sorted following a theoretical framing. The final synthesis in the mapping procedure included a variety of studies (qualitative/quantitative and based on different methodologies, theoretical approaches), but treated based on the key elements studied, and not on the way in which these were studied. The categorisation of key words/main elements, together with the unique identification number followed, makes it possible to find the corresponding reference in the Excel data sheet.

Notes describing parts of the excel sheet is available as a documentation file (Description Excel sheet mapping sectoral level)

Studien är en systematisk kartläggning över litteratur rörande innovation i livsmedelssystemet publicerad i vetenskapliga tidskrifter i perioden 1997-2017 och som rör det agrikulturella kunskaps och innovationssystemet i OECD-länder.
Sammanfattningar från 320 artiklar som ingår i studien har analyserats utifrån nyckelord som sedan kategoriserats och beskrivits med syftet att påvisa de nuvarande kunskapsläget och identifiera framtida forskningsområden. Materialet är kategoriserat i åtta huvudteman: agenter, teknologi, kunskaps- och lärandeprocesser, interaktionsmekanismer, institutioner, slutanvändare, systemförändringar och kontextuella variabler.
Innovation in agri-food systems – A systematic mapping of the literature (1997-2017) - Innovation at system level in agri-food. Meta-table of key elements categorized in mapping study (1997-2017)
Keywords: agriculture; jordbruk; systematic mapping; systematisk kartläggning; Agri-food; agri-food; Agricultural knowledge and innovation system (AKIS); Agricultural knowledge and innovation system (AKIS); innovation systems; innovationssystem; Community, urban and rural life; Lokalsamhälle, stads- och landsbygdsliv; Business/industrial management and organisation; Företags-/industriledning och organisation; Agriculture and rural industry; Jordbruk och landsbygdsnäring; Agricultural and Veterinary sciences; Lantbruksvetenskap och veterinärmedicin; Economics and Business; Ekonomi och näringsliv